2018
DOI: 10.1108/ijshe-12-2016-0225
|View full text |Cite
|
Sign up to set email alerts
|

The cost of sustainability in higher education: staff and student views of a campus food culture

Abstract: Purpose This study aims to investigate the sustainability of the food culture at Deakin University and to determine what the barriers to increasing the sustainability of food on the Burwood campus may be. Design/methodology/approach An online survey of staff and students from the Faculty of Health at the Burwood campus of Deakin University (n = 697) was undertaken. The survey included questions relating to eating habits on campus, views on the current food culture, food security, food disposal, visions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In particular, the availability of sustainable food choices and the perceived effectiveness of individual actions have been shown to be key factors influencing consumers transition from intention to action [23]. One study in an Australian university identified that the major barrier limiting students purchasing of sustainable food is the price of food on campus and the cost of sustainability initiatives [24]. Another Australian study identified that most university students were dissatisfied with the availability of sustainable food for purchase on campus [25].…”
Section: University Students Behaviors Towards Purchasing Sustainable Foodsmentioning
confidence: 99%
“…In particular, the availability of sustainable food choices and the perceived effectiveness of individual actions have been shown to be key factors influencing consumers transition from intention to action [23]. One study in an Australian university identified that the major barrier limiting students purchasing of sustainable food is the price of food on campus and the cost of sustainability initiatives [24]. Another Australian study identified that most university students were dissatisfied with the availability of sustainable food for purchase on campus [25].…”
Section: University Students Behaviors Towards Purchasing Sustainable Foodsmentioning
confidence: 99%
“…Finally, in phase 4 (included), the data referring to the "all years-2019" period were selected-that is, from the first published article on the research topic (1968) to the last full year (2019). In this last phase, 93 The search selected documents from the subfields "title, abstract and keywords", in the period that contains the publication of the first article on the research topic until the last full year (52 years), as has been applied successfully in other analyses [69][70][71]. The representativeness of the sample is based on the proven quality of the Scopus database in relation to the indexing protocol and with the systematic procedures of the search criteria.…”
Section: Methods and Data Selectionmentioning
confidence: 99%
“…; Henderson-Wilson, C.; and Murphy, B., titled "The cost of sustainability in higher education: staff and student views of a campus food culture". It was published in the International Journal of Sustainability in Higher Education (publisher: Emerald Publishing, Bingley, UK), linked to the subject area of Social Sciences (Education, and Human Factors and Ergonomics) [93].…”
Section: Subject Areas and Journalsmentioning
confidence: 99%
“…Baldwin and Chung (2007) and Ahmed et al (2018), for example, both imply that food waste is an ethically fraught issue when many people, including people in developed countries, experience food insecurity. Shaw et al (2018) come closer to a systems view in their article on a campus food culture at Deakin University in Australia. In their survey, a majority of student and staff respondents indicated that the high costs of campus food options, particularly healthy foods, were significant barriers for them.…”
Section: Campus Food Sustainabilitymentioning
confidence: 98%
“…Recent studies of sustainable campus food initiatives have addressed specific aspects of food such as food waste (Baldwin and Chung, 2007;Ahmed et al, 2018) and organic foods (Duram and Williams, 2015;Hamilton and Hekmat, 2018), as well as broader topics such as intentions to adopt sustainable campus dining practices (Chen et al, 2011) and campus food culture (Shaw et al, 2018). Admittedly, none of these studies intends to engage a holistic analysis of campus sustainability.…”
Section: Campus Food Sustainabilitymentioning
confidence: 99%